Developing of micro health takaful of affordable monthly payment for poor community in Malaysia - Fauzilah, Salleh; Puspa Liza, Ghazali; Ahmad Syukri, Yazid; Wan Norhayate, Wan Daud; Roslida, Abdul Razak; Nahidah, Mustaffa; Norizan, Remli (2018)
When somebody participates in medical and health takaful, they will contribute a certain sum of money to a Takaful fund in a form of participative contribution (tabarru‟). The aim of the study is to propose the micro medical and health Takaful framework for poor or lower income which is according to expert opinions. According to the method, participants involvement in the focus group discussion are 10 participants to show a greater potential in discussing but lead by a moderator who followed the predesigned script and the session was in parallel with audio or video recording as evidence. The result from the focus group discussion among expertise which the affordable monthly payment for health microtakaful among poor community is RM20 for outside patient with the total per family is RM30,000 per year (30X) is equal to RM0.667 per RM1, 000 unit. Medical treatment can be made in goverment hospital or private hospital/clinic but the limit expenses is RM30,000. The product can offer 3 packages that the monthly payment for RM5 to RM15 for outside patient per family with differences range of expenses in the microtakaful for medical and health is the best product for poor community income, if it can be implemented in Malaysia as soon as possible.